Recurrent metabolic acidosis: is it by chance? - Naushad, Aleena; Krishnanunni, Sudha; Anand, Manjula; Pachat, Divia; Mohanlal, Smilu (International Journal of Contemporary Pediatrics, 2023)
Succinyl CoA 3 oxoacid CoA transferase deficiency (SCOTD) is an autosomal recessive disorder of ketone body utilization which present with recurrent episodes of metabolic acidosis. We have a 23-month old child who presented with 3 episodes of metabolic acidosis. Each time the toxicology profile came positive for ethyl alcohol. We couldn’t get any history suggestive of poisoning. So we were in a great dilemma and considered the possibility of Munchausen syndrome by proxy and a metabolic cause. Even though the initial genetic result was nonspecific when we reanalyzed the sample for genetic analysis it came positive as Succinyl CoA 3 oxoacid CoA transferase (SCOT) deficiency. The child required intensive care support in all 3 times. We were able to manage the child with supportive measures each time. Now the child is under regular follow up and doing well. SCOTD should be considered in any children presenting as recurrent episodes of metabolic acidosis. The rarity of this disorder will lead to the diagnostic dilemma that we face as like in this case.